The Role of Social Media on Student Consumer Behavior in the City of Bandung - Stephani Putri Kawidjaya; Fandi Ahmad; Ayudhini Azzahra Permatasari (Talenta Publisher, 2022)
The Covid-19 pandemic, which has had a significant impact, is no exception in Indonesia. This pandemic affects human interactions with one another and changes the economy quite significantly. Then there was a change in how to transact from what was previously offline to online and impacted changes in business processes. This research was conducted to see the influence of social media on the behavior of this research using a descriptive qualitative approach in which the researcher made observations through interviews, then observed the field and distributed questionnaires as well as several previous research studies, based on the data obtained, it was reprocessed into rigid information, from the results. Research shows that 85% of consumers come from adolescents aged 18-25 years, where this consumer segmentation has a big role because they actively use social media as a means or media, especially in terms of transactions in E-Commerce, so it does not rule out that shopping and online transactions are currently. This is proliferating in all corners of the world, especially in one of the big cities in Indonesia, namely the City of Bandung.